Pelaksanaan Perjanjian Sewa-Menyewa Lahan Di Area Sekitar Pantai: perjanjian sewa lahan - Desy Rahmadani, Ayu; Rahman, Arief (Private Law, 2024)
This research aims to determine the legal position of the land subject to the rental agreement and to determine the implementation of land leasing in the area around Maluk Beach, West Sumbawa Region. The type of research used is empirical legal research, with the use of the statute approach, conceptual approach, and sociological approach as the methods. The result of this research determines that the legal position of the research object's land is land bordering the coast it is controlled directly by the state. The Pasir Putih village government is utilizing coastal border land supported by the regulations regarding the tourism development master plan for the West Sumbawa district. The land use implementation carried out is a land rental agreement, in the written form by the Pasir Putih village government and signed by the land lessee.